Supramolecular polymer assembly in aqueous solution arising from cyclodextrin host–guest complexation - Wang, Jie; Qiu, Zhiqiang; Wang, Yiming; Li, Li; Guo, Xuhong; Pham, Duc-Truc; Lincoln, Stephen F.; Prud’homme, Robert K. (Beilstein Journal of Organic Chemistry, 2016)
The employment of cyclodextrin host–guest complexation to construct supramolecular assemblies with an emphasis on polymer networks is reviewed. The main driving force for this supramolecular assembly is host–guest complexation between cyclodextrin hosts and guest groups either of which may be discrete molecular species or substituents on a polymer backbone. The effects of such complexation on properties at the molecular and macroscopic levels are discussed. It is shown that cyclodextrin complexation may be used to design functional polymer materials with tailorable properties, especially for photo-, pH-, thermo- and redox-responsiveness and self-healing.
Keywords: cyclodextrin; host–guest; polymer; smart-material; supramolecular